MEDIA LITERACY FOR DISSEMINATION ANTICIPATED FAKE NEWS ON SOCIAL MEDIA - Dedeh Fardiah; Rini Rinawati; Ferry Darmawan; Rifqi Abdul; Kurnia Lucky (Unisba Press, 2020)
Information technology nowadays results in spreading information rapidly. Everyone can easily produce information quickly through several social media, such as Facebook, Twitter, Instagram, or mobile phone messages, such as WhatsApp, Telegram, etc. It is alarming if the information conveyed is inaccurate such as a hoax with a highly provocative title, leading the reader and recipient to obtain a negative opinion. For fighting hoaxes and preventing their negative impacts, the government has adequate legal protection named ITE Law. Apart from the legal product, the government also forms the National Cyber Institution. For example, in West Java, the government has formed West Java Clean Sweep Team (Saber) for Hoaxes, in charge of verifying information distribution in public. The team is built as proactive efforts of the West Java Provincial Government to secure the residents of West Java from disseminating fake news. This article examines how the West Java Saber Hoaxes Team carried out a strategy to minimize the dissemination of fake news (hoaxes) on social media. The research used descriptive studies through in-depth interviews on West Java Saber Hoaxes Team. The result of the research showed that strategies conducted by this team are monitoring, receiving complaints, and educating the public.